Charge transfer dynamics in DNA revealed by time-resolved spectroscopy. Issue 3 (23rd December 2016) - Fujitsuka, Mamoru; Majima, Tetsuro
Abstract : Time-resolved study revealed kinetics of charge transfer in DNA. Abstract : In the past few decades, charge transfer in DNA has attracted considerable attention from researchers in a wide variety of fields, including bioscience, physical chemistry, and nanotechnology. Charge transfer in DNA has been investigated using various techniques. Among them, time-resolved spectroscopic methods have yielded valuable information on charge transfer dynamics in DNA, providing an important basis for numerical practical applications such as development of new therapy applications and nanomaterials. In DNA, holes and excess electrons act as positive and negative charge carriers, respectively. Although hole transfer dynamics have been investigated in detail, the dynamics of excess electron transfer have only become clearer relatively recently. In the present paper, we summarize studies on the dynamics of hole and excess electron transfer conducted by several groups including our own.